2006
DOI: 10.1074/jbc.m605339200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factors Mediate Heterotrimeric G Protein-dependent ERK1/2 Activation by Transactivating Sphingosine 1-Phosphate Receptors

Abstract: Although several studies have shown that a subset of insulin-like growth factor (IGF) signals require the activation of heterotrimeric G proteins, the molecular mechanisms underlying IGF-stimulated G protein signaling remain poorly understood. Here, we have studied the mechanism by which endogenous IGF receptors activate the ERK1/2 mitogen-activated protein kinase cascade in HEK293 cells. In these cells, treatment with pertussis toxin and expression of a G␣ q/11 -(305-359) peptide that inhibits G q/11 signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 59 publications
(80 reference statements)
6
64
0
1
Order By: Relevance
“…7B shows the effects of PTX on IGF-stimulated ERK1/2 activation. Consistent with our previous observations (31,38), pretreatment with PTX inhibited IGF-1-, IGF-2-, and S1P-stimulated ERK1/2 phosphorylation by 47, 66, and 73%, respectively. PMA-stimulated ERK1/2 activation was not affected.…”
Section: Igf-1 and Igf-2/m6p Receptors Employ A Common Sphingosine Kisupporting
confidence: 80%
See 4 more Smart Citations
“…7B shows the effects of PTX on IGF-stimulated ERK1/2 activation. Consistent with our previous observations (31,38), pretreatment with PTX inhibited IGF-1-, IGF-2-, and S1P-stimulated ERK1/2 phosphorylation by 47, 66, and 73%, respectively. PMA-stimulated ERK1/2 activation was not affected.…”
Section: Igf-1 and Igf-2/m6p Receptors Employ A Common Sphingosine Kisupporting
confidence: 80%
“…We have previously shown that both IGF-1 and IGF-2 promote membrane translocation and activation of SK1, increase intracellular and extracellular S1P levels, and activate G protein-coupled S1P receptors in HEK293 cells (31). What remains unclear is how these two structurally distinct receptors activate SK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations